(untitled) (International Journal of Engineering and Computer Science, 2017)
With the advent of Information Technology into almost every aspect of our lives, are we all really able to benefit from it? This paper proposes a way to boost the success of government Schemes for Rural Development using kiosks. In the paper, a solution is discussed that addresses the problem of government schemes not reaching their full potential via awareness among each and everyone, and attempts to resolve it by using kiosk machines, to supply information regarding government schemes. The main purpose is to provide information regarding government schemes to even those rural residents who can barely interact with an electronic device. To do so, a very simple and easily understandable interface has been introduced in the paper. This interface may also provide audio/visual aid. Using this, a person may also get a token, using his/her aadhar card number, to meet with the respective office to proceed for a scheme. In the later versions, feature to transfer a particular page onto the persons mobile phone can also be added.